Determinants of halal purchase intention: case in Perlis / Aflah Isa@Darami, Noorafzainiza Afendi & Farah Lina Azizan - Isa@Darami, Aflah; Afendi, Noorafzainiza; Azizan, Farah Lina (2014)
This study is conducted in the purpose of understanding the relationship between attitude, subjective norms and perceived behavioural controls and the way it influenced the purchase intention of Halal products among consumers. This chapter contains the discussions on the background of the study, problem statement, scope of study, research question, research objectives, significance of the study, definations of key terms and organization of the study.